Design of Real-time Communication Adapter for Different Protocol Sensors in Sensor Web - Xuefeng Liu; Jing Zhu; Jianhua Mao; Xiaoming Shao; Longlong Lu (Institute of Advanced Engineering and Science, 2012)
A real-time communication adapter named SensorAdapter is designed to communicate between different protocols sensors and data service layer in Sensor Web. The adapter is extended and restructured based on SensorBus, an open source project raised by a German company called 52north. By structuring the receiving module and extending the proxies of sensors according to the communication protocols the sensors use, the adapter can receive sensing information detected by different protocols sensors simultaneously. The receiving module identifies a sensor and finds its corresponding proxy in SensorAdapter by sensor ID (SensorID), and then packages the sensing information to XMPP messages and sends them to XMPPServer by invoking the methods in its proxy. At last, an example of SOS is achieved to verify the effect of the adapter. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1357